Approaching tourism communication with empirical multimodality: exploratory analysis of Instagram and website photography through data-driven labeling - Mattei, Elena (Frontiers in Communication, 2024)
This paper reports the methods and results of the manual annotation of visual features in two corpora of tourism photography on travel boards' digital channels with a tailored tagging model based on the Grammar of Visual Design (Kress and van Leeuwen, 2006) and adapted to tourism discourse. Computational analysis and statistical modeling show how the testing of theoretical assumptions through categorized data may lead to evidence-based interpretations of patterns of data clustering and to the detection of new communicative aims and conventions across digital media (Stöckl et al., 2020; Mattei, 2023a). Preliminary findings reveal indeed significant differences in the frequency of tag (co)patternings and use of visual strategies across channels that are related to the role and aim of each channel in the marketing funnel of persuasion and journey towards purchase (AIDA). Instagram imagery was demonstrated to foster a pre-consumption of the travel experience and emotionally charged reactions by representing perceptive and emotive expectations. While both channels play on postmodern tourists' desire for the uncontaminated, remote and the authentic (Urry and Larsen, 2011), Instagram favors aerial views of pristine, aesthetically pleasant settings, often complemented with rear views of solitary individuals performing static processes of contemplation of natural wonders. This suggests a focus on attracting the attention and providing instant gratification of the senses by representing what stands in contrast to everyday life and traditional tourist experiences, both avoiding cognitive effort in a pervasive digital sphere with endless sources of information and encouraging further exploration on websites.